Two-orbital model for interference of pseudo-gaps in the superconducting state of iron-based superconductors. (May 2021) - Pradhan, B.; Parida, P.K.; Sahoo, S.
Abstract: The coexistence of different order parameters and the pairing symmetry is the major issue in the study of iron-based superconductors. We adopt a two-orbital tight-binding model, for the coexistence of superconductivity, Jahn–Teller distortion and antiferromagnetism in s ± -wave symmetry, which is consistent and most favourable for the nearest-neighbour pairing interaction, and derive a set of gap equations which are solved numerically and self-consistently. The effects of the order parameters on one another are studied. We have also calculated the electronic specific heat, density of states and band energies. The specific heat jump at the transition temperatures showing the second order phase transitions is observed and the coefficient of specific heat is also calculated. The density of states shows the defined interference peaks on either side of the Fermi level corresponding to the order parameters with van Hove singularities. The band energies which show the saddle point shift of the bands are also studied. Highlights: A Hamiltonian for Fe based SCs with SC, JT and AFM interactions is proposed. Zubarev's technique of double time Green's function technique is used. The interplay of the gap parameters are studied. The gap values are observed through DOS plots. Specific heat jump is observed at the transition temperatures. Band energies are also studied.